Targeting Ca2+ release-activated Ca2+ channel channels and leukotriene receptors provides a novel combination strategy for treating nasal polyposis. - Di Capite, J; Nelson, C; Bates, G; Parekh, A (2009)
BACKGROUND: Nasal polyposis is a chronic inflammatory disease of the upper respiratory tract that affects around 2% of the population and almost 67% of patients with aspirin-intolerant asthma. Polyps are rich in mast cells and eosinophils, resulting in high levels of the proinflammatory cysteinyl leukotrienes. OBJECTIVES: To better understand the role of the proinflammatory leukotrienes in nasal polyposis, we asked the following questions: (1) How do nasal polyps produce leukotriene C(4) (LTC(4))? (2) Can LTC(4) feed back in a paracrine way to maintain mast cell activation? (3) Could a combination therapy targeting the elements of this feed-forward loop provide a novel therapy for allergic disease? METHODS: We have used immunohistochemistry, enzyme immunoassay, and cytoplasmic calcium ion (Ca(2+)) imaging to address these questions on cultured and acutely isolated human mast cells from patients with polyposis. RESULTS: Ca(2+) entry through store-operated Ca(2+) release-activated Ca(2+) (CRAC) channels in polyps produced LTC(4) in a manner dependent on protein kinase C. LTC(4) thus generated activated mast cells through cysteinyl leukotriene type I receptors. Hence Ca(2+) influx into mast cells stimulates LTC(4) production, which then acts as a paracrine signal to activate further Ca(2+) influx. A combination of a low concentration of both a CRAC channel blocker and a leukotriene receptor antagonist was as effective at suppressing mast cell activation as a high concentration of either antagonist alone. CONCLUSION: A drug combination directed against CRAC channels and leukotriene receptor antagonist suppresses the feed-forward loop that leads to aberrant mast cell activation. Hence our results identify a new potential strategy for combating polyposis and mast cell-dependent allergies.